Redefining Character Education: A Review of Essential Goals and Values - Vinna Dinda Kemala; Alil Rinenggo; Ary Purwantiningsih; Vinni Dini Pratiwi (Academy of Education Journal, 2026)
In one decade lastly, education character experience shift significant conceptual​ along increasing complexity challenge social, cultural, and global. This article aim for reconstruct understanding education character through review systematic to goals and values growing essentials​ in literature academic cutting-edge research this use approach systematic literature review to article journal reputable and source policy relevant education, with​ analysis thematic for identify patterns, tendencies, and redefinitions conceptual education character contemporary. Findings study show that education character no again understood as planting individual moral values that are normative and static, but rather as approach education holistic that integrates moral, social, emotional and civic dimensions in a way simultaneously. Core values such as honesty, responsibility responsibility, fairness, caring, respect, and citizenship show consistency cross context culture and country, but redefined as competence behavior that can developed through experience planned learning, culture​ supportive schools, as well as practice pedagogical reflective. This study also confirms convergence between education character and social-emotional learning, which strengthens view that character nature dynamic, relational, and evolving through interaction sustainable social. With​ thus, the article this offer framework conceptually broadening​ understanding education character as an educational process contextual and adaptive sustainability, at the same time give implications theoretical and practical for development curriculum as well as policy education characters in the 21st century.